Climate Change: Models and Impact in the Mediterranean´s Food Security - García, David; Herrero, Rubén (UNISCI Discussion Papers, 2014)
Climate change is a reality in the global society. This article examines its possible effects on the North African area. In the text, the main models of climate change related to the Mediterranean region are presented as well as the problems and limitations posed by such models and the various fore castings on possible effects on the central Maghreb region. The article tries to show how the Maghreb food security will be affected.